2005
DOI: 10.1086/432047
|View full text |Cite
|
Sign up to set email alerts
|

Predicted Light Curves for a Model of Solar Eruptions

Abstract: We determine the thermal radiation generated by a loss-of-equilibrium model for CMEs and eruptive solar flares. The magnetic configuration of the model consists of an outward-moving flux rope with a vertical current sheet below it. Reconnection at the sheet releases magnetic energy, some of which is converted into thermal energy that drives chromospheric evaporation along the newly connected field lines exiting the current sheet. The thermal energy release is calculated by assuming that all of the Poynting flu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(51 citation statements)
references
References 38 publications
2
49
0
Order By: Relevance
“…The ratio between both magnetic powers is more than two orders of magnitude. Under the assumption that the same ratio holds for SXR emissions (which is not trivial since it depends on the reconnection rate, see Reeves & Forbes 2005), our scalings are consistent with relatively older (resp. younger) ARs producing C-class (resp.…”
Section: Energetics and Time-scalessupporting
confidence: 71%
See 2 more Smart Citations
“…The ratio between both magnetic powers is more than two orders of magnitude. Under the assumption that the same ratio holds for SXR emissions (which is not trivial since it depends on the reconnection rate, see Reeves & Forbes 2005), our scalings are consistent with relatively older (resp. younger) ARs producing C-class (resp.…”
Section: Energetics and Time-scalessupporting
confidence: 71%
“…Several 2.5D MHD simulations for flares and CME early phases have calculated the magnetic and thermal properties of this standard model (e.g. Amari et al 1996;Chen & Shibata 2000;Linker et al 2003;Reeves & Forbes 2005;Shiota et al 2005;Jacobs et al 2006). They confirmed the cartoons, and successfully explained many observed properties.…”
Section: Introductionmentioning
confidence: 65%
See 1 more Smart Citation
“…The CME velocityḣ that is deduced by integrating equations (2)Y(5) with the initial conditions given in equations (7) could be an upper limit, since we treat the CME as a projectile in our calculations (e.g., , and all the magnetic energy released is assumed to be used in speeding up the CME. Recently, Reeves & Forbes (2005) studied the heating features associated with CME motions and found that including the thermal energy and evaporation in the catastrophe model does not change our previous results because only the work done by the magnetic force on the flux rope affects the trajectories.…”
Section: Various Components Of Cme Speedsmentioning
confidence: 74%
“…Because of the gap in SXT observations, we cannot rule out the possibility that the flare site was behind the limb and thus partially occulted. However, as shown most recently by Aarnio et al (2010), it is possible to have powerful and massive CMEs associated with relatively weak flares (see also Reeves & Forbes 2005). (Scherrer et al 1995) takes high spectral resolution images of the Ni i λ6768 absorption line to characterize velocity oscillations and Zeeman splitting in the photosphere.…”
Section: Yohkoh/sxt Observationsmentioning
confidence: 90%